Study of diesel engine exhaust emission - Zong, Zijing (2014)
The use of diesel engine for on-road and off-road vehicles has become more common and economical as compared to gasoline engine due to low cost of diesel fuel and low fuel consumption rate. The negative impact of over-relying on diesel engine is the generation of harmful pollutant such as carbon monoxide, Nitride oxide, Particulate matter etc. These pollutants will not only pose danger to the environment but also will cause human to suffer a detrimental effect on their body. Reduction of exhaust emission from motor vehicle will be a considerable interest in the coming year in view of increasing concern regarding environmental protection and stringent exhaust gas emission. Therefore, the greatest challenge face by automotive industry is to design diesel engine which not only have the capability of improving fuel economy, but also able to conserve natural resources and limit pollutants emission. To compromise these conditions, it will require new materials, new lubricants and low-emissions fuel. The first part of the investigation will deals with the influence of engine oil/lubricant on exhaust emission and the second part of the investigation will deals with effect of adding additives on diesel engine. Based on previous research, engine lubricants help to improve efficiency but contribute to engine exhaust emissions. Investigations have shown a clear effect of engine oil on emissions, which depends on the properties of lubricants which include lube oil characteristic, sulphur contents, metal contents, volatility and density. Relevant research has also determined that modification of diesel properties by adding additives will not only improve the fuel consumption rate but also able to control diesel emission. The results have shown a distinct improvement by mixing the additives with diesel fuel.